The personal calculus of moral reasoning and identity in global health professions work - Razack, Saleem Idris (Canadian Medical Education Journal, 2017)
In this personal essay, the author reflects on experiences in global health professions education projects, and the moral reasoning that might be required to define explicitly what constitutes ethical participation. Three interrelated notions are explored: The decision to engage or not through a discussion of the concepts of safety, understanding power dynamics, and analysis of personal and institutional motivations for the project The ultimate goals to promote human flourishing and improve equity, through attention to local inequities potentially experienced by either participants or colleagues from home. Attention to the personal transformative potential of participation in global health professions projects. A framework for exploring moral reasoning in global health professions education work using these three concepts is presented as one that the author has found helpful in his own work in global health professions education.